The Found of Causal Conjunction in Kaylnn Bayron “This Wicked Fate” Novel - Komang Sri Anjayani; Ni Wayan Suastini (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Causal conjunctions play a crucial role in building relationships between propositions in literature. This research analyzes the types and functions of causal conjunctions in conveying cause-effect relationships. The study uses data from Kaylnn Bayron's novel "This Wicked Fate" to offer a unique perspective on causal conjunction usage. Data collection employed the observation method to identify types and functions of causal conjunctions. This was followed by descriptive qualitative analysis. Findings were presented using both formal and informal methods. The analysis identified four types of causal conjunctions. These include general causal relations (10 data), specific causal relations (3 data), conditional relations (26 data), and general reversed causal relations (20 data). Conditional relations emerged as the most prevalent type. Functionally, the study observed 36 data of external function and 23 data of internal function. The external function was found to be predominant. This research demonstrates how causal conjunctions form logical sentences. It reveals the ways authors express cause and effect through various conjunction types and functions. The study contributes to our understanding of how causal relationships are linguistically constructed in literary texts. It provides insights into the nuanced use of language in narrative contexts.